High-moisture sorghum for growing-finishing swine - Trotter, M.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty-seven crossbred pigs (averaging 95 pounds initially) were used to compare the value of sorghum grain harvested with high-moisture and stored in an oxygen-limiting structure with that harvested with high-moisture and treated with propionic acid (1.2%), and stored in a metal bin, or field dried. Average daily gain, average daily feed intake, and feed/gain ratios in a growth trial and protein and energy digestibilities in a digestion trial, showed that high-moisture sorghum grain and field-dried sorghum have equal feeding values when compared on a dry-matter basis.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; High-moisture sorghum; Growing-finishing pigs; Energy digestibilities; Propionic acid